Identifying Domestic and Imported Core Inflation - Bjornland, Hilde (Washington, D.C. : International Monetary Fund, 2000)
This paper estimates core inflation in Norway, identified as that component of inflation that has no long-run effect on GDP. The model distinguishes explicitly between domestic and imported core inflation. The results show that (domestic) core inflation is the main component of CPI inflation. CPI inflation, however, misrepresents core inflation in some periods. The differences are well explained by the other shocks identified in the model, in particular the oil price shocks of the 1970s when Norway imported inflation, and the negative noncore (supply) shocks of the late 1980s, which pushed inflation up temporarily relative to core inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet